Proposal of a new technique for bile duct reconstruction after iatrogenic injury: study in dogs and review of the literature - Crema,Eduardo (2007)
PURPOSE: Interposition of a jejunal tube between the common bile duct and duodenum. METHODS: Five adult mongrel dogs of both sexes, weighing on average 22.3 kg (18 to 26.5 kg), were used. Obstructive jaundice was induced by ligation of the distal common bile duct. After one week, a 2.5-cm long jejunal tube was fabricated from a segment of the loop removed 15 cm from the Treitz angle and interposed between the common bile duct and duodenum. RESULTS: The animals presented good clinical evolution and no complications were observed. After 6 weeks, complete integration was noted between the bile duct mucosa, tube and duodenum and a significant reduction in total bilirubin and alkaline phosphatase was observed when compared to the values obtained one week after ligation of the common bile duct. CONCLUSION: The jejunal tube interposed between the dilated bile duct and duodenum showed good anatomic integration and reduced total bilirubin and alkaline phosphatase levels in the animals studied.